دور السياق القرآني في تحديد دلالات آيات الوعيد: The Role of Quranic Context in Determining Signs of Verses of Threat - Al Tahan, Hudhayfah Abdul Rahim; Elatrash, Radwan Jamal (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف البحث إلى تسليط الضوء على أهمية دور السياق في تحديد فهم معاني القرآن الكريم وبالذات دلالات آيات الوعيد. كما تؤكد هذه المقالة على خطورة إهمال السياق القرآني في العملية التفسيرية، لأن ذلك من الأسباب الأكيدة في تعثر الجهود في الوصول إلى فهم صحيح لموضوعات القرآن، وبالذات موضوع الوعيد، وعليه فإن نجاح العملية التفسيرية وتحقيق الهدف المنشود مرهون بدرجة استخدام السياق كآلة تفسيرية ضرورية. ومهما يكن من أمر، فقد تم استخدام منهجين أساسيين لتحقيق الأهداف المحددة لهذا البحث، الأول هو المنهج الاستقرائي، الذي تم من خلاله جمع وتصنيف ومراجعة النصوص القرآنية ذات الصلة، والثاني هو المنهج التحليلي، حيث تم تفحص تأثير السياق على فهم آيات الوعيد وكيفية تفسيرها وتحديد دلالاتها بشكل عملي. هذا وقد أسفر البحث عن نتائج مهمة تبرز أهمية السياق في فهم معاني آيات الوعيد وبيان خطورة إهمال استخدامه باعتبار ذلك سبباً وراء تعثر الجهود في فهم موضوعات القرآن وتفسيرها بشكل صحيح وبالذات آيات الوعيد. ABSTRACT The research aims to highlight the importance of the role of context in determining the understanding of the meanings of the Holy Qur’an, especially the meanings of the verses of threat. This article also emphasizes the danger of neglecting the Qur’anic context in the interpretive process, because this is one of the sure reasons for the failure of efforts to reach a correct understanding of the topics of the Qur’an, especially the subject of threat. Therefore, the success of the interpretive process and achieving the desired goal depends on the degree of use of context as a necessary interpretive tool. Whatever the case, two basic approaches were used to achieve the specific objectives of this research. The first is the inductive approach, through which the relevant Qur’anic texts were collected, classified and reviewed. The second is the analytical approach, where the influence of context on understanding the verses of threat and how to interpret them was examined. Defining its meanings in a practical way. The research yielded important results that highlight the importance of context in understanding the meanings of the verses of threat and demonstrate the danger of neglecting its use as a reason behind the faltering efforts in understanding and interpreting the topics of the Qur’an correctly, especially the verses of threat.